Analisis Kinerja Badan Pengelolaan Keuangan dan Aset Daerah (BPKAD) Kota Metro - Yulita Zanaria; Aris Sunyoto (Institut Informatika Dan Bisnis (IIB) Darmajaya, 2018)
The purpose of this study is to describe the performance of the Metro City Asset Financial Management Agency (BPKAD) in managing regional assets. As the Regional General Treasurer, BKAD is a technical service that is responsible for receiving regional income and issuing money for regional needs through regional general cash. With the regional treasury, a region can manage the availability of sufficient funds to finance regional expenditures. In the regional general cash, it can also be seen how much wealth a region has. Regional cash itself is contained in the comparative balance sheet which is part of the financial statements. The results of the research in cash management have received regional income and disbursed funds used for regional expenditure purposes. The procedure for cash receipts and disbursement of funds directly handled by the regional cash management section is regulated in the guidelines for managing the business implementation of the Metro City APND and so far the cash management section has carried out its duties in accordance with these guidelines. In general, Metro City BPKAD's performance in managing lancer beum assets is said to be good and still not optimal, this can be seen based on indicators used in BPKAD's performance appraisal in managing transparent assets, namely accountability, transparency, economy, efficiency and effectiveness. regional income that goes into regional treasury has increased.Keywords-Performance